Post Banding Ulcer Haemorrhage: a Contributor to Morality in Patients with Liver Cirrhosis - Perveen, Shahida; Ahsan, Omar; Butt, Batool; Abbas, Atif; Asif, Sehrish Jahan; Hassan, Syeda Fatima (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To evaluate the frequency, risk factors and mortality of post-banding bleeding in cirrhosis.Study Design: Retrospective longitudinal Study.Place and Duration of Study: Department of Medicine, Fauji Foundation Hospital, Rawalpindi Pakistan, from Feb to Jul 2021.Methodology: Esophageal variceal band ligation (EVBL) was done in 123 patients. The study cohort was divided into two groups: Group-1 without re-bleed and Group-2 with re-bleed. Blood chemistry, Child-Pugh and MELD score, including the indications of EVBL and risk factors, were also analysed. Regression analysis was performed.Results: Re-bleed occurred in 10.6% (n=13) of patients. The mean duration between ligation and re-bleed was 8.75±2.8 days. Oesophageal ulcers were the most common cause of re-bleeding (38.5%). Mortality rates among the two groups were 21.8 %( n=24) and 30.8 %( n=4), respectively. The model for end-stage liver disease score (OR 2.177, CI 1.069-4.43, p .03), APTT (OR 0.593, CI 0.397-0.887, p .01) and Sodium (OR 1.345, CI 1.07-1.69, p